Touring the Low Countries : accounts of British travellers 1660-1720 - Van Strien, Kees; De Vries, Dirk (Amsterdam : Amsterdam university press, 1998)
'Touring the Low Countries' is an anthology of approximately forty travel documents by British tourists - journals, letters, and financial accounts - most of them published here for the first time. The United Provinces and the Spanish Netherlands, with all the variety of their contrasting cultural climates, were regarded as an ideal destination for a short trip abroad. A six weeks' tour through Holland, Brabant and Flanders could be just as educational and enjoyable as a Grand Tour, which for most people was financially out of reach. More direct and colorful than any analytical study of the subject, this book presents the reader with images of the Low Countries that the tourists wished to convey to their contemporaries at home. The anthology will appeal both to students of travel and to those interested in the cultural history of the Low Countries. It offers a wealth of new information on social and artistic life in Holland and Flanders.
Includes bibliographical references and indexes.
Keywords: British -- History -- 17th century -- Belgium; British -- History -- 17th century -- Netherlands; Belgium -- Description and travel; Netherlands -- Description and travel